ANALISIS ANTESEDEN YANG MEMPENGARUHI NIAT BELI ON-LINE PADA TOKOPEDIA.COM - Nur Rokhim; Fitroh Adhilla (Universitas Ahmad Dahlan, 2015)
This research was conducted to examine the antecedents that affect online purchase intentions. The sample used in this study amounted to 71 respondents. The sampling method using purposive sampling. Data analysis method used is quantitative analysis using validity and reliability tests, F tests, coefficient of determination, t tests and multiple regression analysis. By using the multiple regression method it can be concluded that the web design variable does not have a positive and significant effect on online purchase intention with a significance value (P Value) of 0.324> 0.05. While reliability has a positive and significant effect on online purchase intentions with a significance value (P Value) of 0.018 <0.05. responsiveness has a positive and significant effect on online purchase intentions with a significance value (PValue) of 0.061> 0.05. The guarantee has a positive and significant effect on online purchase intention with a significance value (P Value) of 0.815> 0.05. For ordering a positive and significant effect on online purchase intentions with a significance value (P Value) of 0, 002 <0.05. Simultaneously web design, reliability, responsiveness, guarantee, and ordering have a significant effect on online purchase intention with an F count of 5.960 with a significance value (P Value) of 0.000 <0.05. The resulting determination coefficient is 0.246, which means that 24.6 percent of changes in the online purchase intention variable are explained by changes in web design variables, reliability, responsiveness, guarantees, and bookings together, while the remaining 76.4 percent is explained by other variables which is not included in this study.